Effects of Liquidity Risk Management and the Financial Performance of Savings and Credit Cooperative Societies in Embu County - Mwanthi, Faith Kaluki (University of Embu, 2019)
The financial sector comprises of various institutions such as banks, micro finance institutions, Sacco's, pension schemes among others. Sacco's have i11 a great way helped in the improvement and also growth of the Kenyan economy. They have put their focu mostly to the low income households and also the unemployed. This has helped them acquire loan and also have a chance also to save their income however this has had its negative effects where Sacco's have been highly exposed to liquidity risk. Sacco's have not been able to tackle this risk where some Sacco's have been registering low returns due to liquidity risk. This study was therefore taken so as to relate liquidity risk and financial performance of Sacco's and also give a recommendation of what they can do so as to reduce its negative effects. The specific objectives of undertaking this research study include; to determine the effects of liquidity management on financial performance of Sacco's in Embu County Kenya, to establish the effect of credit risk policy on financial performance of SACCO's and to analyze the asset quality on the financial performance of SACCO's in Embu County, Kenya. The specific objectives are the coefficients for the independent variable in the study that is liquidity risk. In the study, financial performance is the dependent variable. The research design being used in this study is a descriptive research design. The data collection instruments in this case include self-administered questionnaires which are used to ex.tract valuable primary data from the Sacco' ' management. The study will use quantitative method to analyze the data and review the simultaneous impact of the independent variables on the dependent variable.